The Application of AI-Assisted Project-Based Learning to Improve Students' Critical Thinking Skills - Bahrul Alim; Butsiarah Butsiarah (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to test the effectiveness of applying the Project-Based Learning (PJBL) model supported by Artificial Intelligence (AI) technology in improving the critical thinking skills of students in the Physical Education, Health, and Recreation (PJKR) study program. The study uses a quasi-experimental design with two groups: the experimental group, which receives PJBL-AI-based learning, and the control group, which follows conventional learning based on lectures and guided discussions. The results show that the implementation of the PJBL-AI model significantly improves students' critical thinking skills. The experimental group showed an average posttest score increase of 92.3, while the control group experienced only a small increase, with a posttest score of 85.2. The use of AI in project-based learning also enhanced student engagement in discussions, collaboration, and strengthened their reflective critical thinking process. AI technologies such as ChatGPT and Canva AI helped students in designing, evaluating, and formulating arguments in a more systematic and creative manner. These findings suggest that the combination of PJBL and AI is highly effective in enhancing students' critical thinking skills in the context of physical education, offering practical solutions for improving learning quality.